Myricetin Inhibits Islet Amyloid Polypeptide (IAPP) Aggregation and Rescues Living Mammalian Cells from IAPP Toxicity - Zelus, Casey (Bentham Open, 2012)
The aggregation of the amyloidogenic polypeptide IAPP (Islet Amyloid Polypeptide, amylin) is believed to play a direct role in the death of pancreatic β-islet cells in type II diabetes. Preventing the initial aggregation event of IAPP is one strategy for slowing, and possibly preventing, the progression of this disease. Here, we investigate myricetin’s potential as an inhibitor of IAPP aggregation. We show that myricetin prevented thioflavin T binding in a concentration dependent manner. Atomic force microscopy revealed that myricetin prevented fiber formation under rigorous conditions conducive to forming IAPP aggregates. Using an IAPP-EGFP (Enhanced Green Fluorescent Protein) protein construct, we find that high concentrations of myricetin slowed the in vivo aggregation of IAPP-EGFP. Myricetin was also found to rescue living mammalian cells from the toxic effects of IAPP. These results indicate that myricetin is a strong inhibitor of IAPP amyloid aggregation and a potential lead molecule for the development of an amyloid inhibiting therapeutic.